Case reportSimvastatin-induced rhabdomyolysis: a case study on clinical-decision making based on the evidence-based medicine approach - Koskinas, Konstantinos; Tzellos, Thrasyvoulos G.; Gougoulias, Kyriakos; Gougoulias, Georgios; Papakonstantinou, Christos; Kouvelas, Dimitrios (Archives of Medical Science, 2007)
A case of a woman diagnosed to have rhabdomyolysis is presented. It was attributed to simvastatin she had been receiving for 1 year. Based on pathogenesis and medical examination, the diagnosis of statin-induced rhabdomyolysis was made. Simvastatin was discontinued with concomitant clinical improvement followed by serum creatine kinase decrease. Future course of therapy was decided after reviewing the literature using evidence-based medicine tools. The purpose of this case report is to share our experience so that physicians are reminded of the potential of rhabdomyolysis related to statin use and illustrate the value of evidence-based medicine in clinical practice.